Anticoagulation and bleeding events in Patients with Post- Operative Atrial Fibrillation After Cardiac Surgery. (14th October 2021) - Alam, Z; Porudominsky, R; Lo Presti, S; Li, V; Rodriguez-Correa, C; Glymph, D.C; Arenas, I
Abstract: Background: Post-operative atrial fibrillation (POPAF) following cardiac surgery is a common arrhythmia associated with an increased morbidity and mortality. There is little data evaluating the safety and effectiveness of anticoagulation (AC) in POPAF patients. We investigated the occurrence of 30-days POP major bleeding or embolic events and their timing in relation to the index cardiac surgery, the initiation of the arrhythmia and of anticoagulation in patients who developed new onset POPAF. Methods: 4, 073 consecutive patients undergoing cardiac surgery from September 2010- December 2016 were evaluated. Patients with history of AF/Aflutter were excluded. POPAF was confirmed by ECG or telemetry. Major post-operative bleeding that occurred after AF was defined using PLATO criteria or the BARC scale (any ≥3). Results: 3, 230 patients were included (37% CABG, 69% valve surgery). The incidence of POAF was 24%. The median time (IQR) of POPAF was 3 (2) days after the index surgery. 64% of POAF patients were male and 14% had a history of stroke. The mean (SD) age was 72 (9) years old. The average (SD) CHA2DS2-VASc score was 3.9 (1.5). The initial postoperative AC was full dose heparin, lovenox or argatroban in 58% of patients. The rest of patients had low dose heparin/lovenox for DVT prophylaxis and/or were started on oral anticoagulation without a bridge. The median (IR) time of POPAF to anticoagulation was 1 (2) days. There were 15 (1.9%) major bleeding events; 88% of which occurred in patients receiving full anticoagulation. Major bleeding events occurred a median of 15 (9) days after the index surgery and 9 (6) days after anticoagulation. Independent predictors of major bleed were history of PAD (P<0.01) and pre-operative use of b-blockers (P=0.04). There were 11 (1.4%) POP strokes which occurred a median of 5 (16) days after the index surgery, and 2 (13) days after POPAF. 63% of strokes happened in patients that received anticoagulation. The mean CHA2DS2-VASc score were 3.9 (1.5) and 4.7 (1.7), P=0.1 for patients without and with strokes, respectively. Stroke history (P<0.01) was the only independent stroke predictor. Both strokes and bleeding events were associated with significantly longer ICU and hospital length of stay. 86% of POPAF patients received amiodarone during hospitalization and 2.1% electric cardioversion. Upon discharge, 2.3% of patients were in in atrial fibrillation and 0.8% in atrial flutter. Conclusion: The post-operative course of major bleeds and stroke in patients with POPAF after cardiac surgery is different. Bleeding events are delayed and appear related to anticoagulation. The relative benefit of perioperative anticoagulation remains unclear. Funding Acknowledgement: Type of funding sources: None.